Caminhos estratégicos para o desenvolvimento rural sustentável: uma análise da dinâmica sociotécnica dos quintais produtivos - Abrantes, Karla Karolline de Jesus (2015)
The present study, inserted in the research line "public policies and sustainable Rural Development", analyzes the dynamics of sociotechnical productive backyards, from experiences of family farmers benefited by the project "Backyards for life". The project is coordinated by the non-governmental organization (NGO) "Centre of Labor Studies and Worker‟s Counseling” (CETRA, portuguese acronym). The central idea of sociotechnical approach aims at uncovering the main requirements of the technological system and the possible influences of these on the performance of the social system, so that the effectiveness of the production system will depend on the suitability of the total social system to meet the requirements of technical system. Thus, for the understanding of this work we will have as object of study the social productive backyard technology which is seen as an instrument that introduces and rescue cultural values and identity of the rural families inherent in spaces around the house. Through a qualitative research, preceded by a case study, we seek to detect the importance and influence of the project on the daily life of farmers. In the hypothesis of considering social productive backyard technology as a strategy for sustainable rural development, based on the principles of Agroecology, the socioeconomics of solidarity and food safety, seeks to identify the environmental, socio-cultural and socioeconomic changes that affect the life of nine (9) benefited families, located in five communities of two municipalities in the Citizenship Territory of Ceara – Vale do Curu and Aracatiaçu in Ceará. For the analysis the study was based on authors such as Navarro (2001), Schneider (2010), Veiga (2001), Altieri (1998), Gliessman has given (2000), Mackin (2007), Mark (2001), Arroyo and Schuch (2006), Singer (2002), Dagnino, Barron and Nana (2010). The trajectories, senses and meanings of the subject researched, parsed from the semi-structured interviews revealed that relevant transformations occurred in the reality of the benefited families. The changes were characterized by innovations and continuities, i.e. by the improvement and replacement of conventional practices and reduction in the use of external inputs, producing, selling and consuming in an ecologically viable way, thus increasing the diversity of production once restricted to cassava, corn and beans and, in the case of vegetables, coriander and chives. It appears to be possible to build relations of coexistence with nature based on environmental sustainability and life quality assurance implementing appropriate economic activities. Considering the importance of this research today, for its purpose of eliciting new reflections on the practices and sociotechnical dynamics to the Academy, organized civil society and to the farmers, we look forward to identifying and analyzing the dimensions of the proposed development. This study may also contribute to the redesign of projects and social policies geared towards family agriculture in the State of Ceará and subsidizing their public bodies and NGOs, with regard to its environmental socioeconomic and sociocultural dimensions, brought about in this study on social technology and productive backyards.